2011
DOI: 10.1186/1741-7015-9-46
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of user groups' perspectives of barriers and facilitators to implementing electronic health records: a systematic review

Abstract: BackgroundElectronic health record (EHR) implementation is currently underway in Canada, as in many other countries. These ambitious projects involve many stakeholders with unique perceptions of the implementation process. EHR users have an important role to play as they must integrate the EHR system into their work environments and use it in their everyday activities. Users hold valuable, first-hand knowledge of what can limit or contribute to the success of EHR implementation projects. A comprehensive synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
295
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 295 publications
(332 citation statements)
references
References 68 publications
15
295
1
7
Order By: Relevance
“…Several studies concluded that time-insufficiency and heavy workload in healthcare sector were considered important factors negatively affecting the adoption of HIS (Boonstra & Broekhuis, 2010;McGinn et al, 2011). On the other hand, other researchers did not find a significant effect of workload as a job stressor (Calisir, Gumussoy, & Iskin, 2011;Dagnone et al, 2006).…”
Section: Environmental Dimensionmentioning
confidence: 86%
See 4 more Smart Citations
“…Several studies concluded that time-insufficiency and heavy workload in healthcare sector were considered important factors negatively affecting the adoption of HIS (Boonstra & Broekhuis, 2010;McGinn et al, 2011). On the other hand, other researchers did not find a significant effect of workload as a job stressor (Calisir, Gumussoy, & Iskin, 2011;Dagnone et al, 2006).…”
Section: Environmental Dimensionmentioning
confidence: 86%
“…As hypothesized, WOL was found to have a significant negative effect on the use of HIS inside the hospital and its effect was the largest among the environmental factors in this study. Other studies also concluded that heavy workload can cause staff to develop negative attitudes towards the adoption of new technologies (Boonstra & Broekhuis, 2010;Kale & Goh, 2014;McGinn et al, 2011). Vendor support and post-deployment services was also found to be a significant contributor to foster the adoption of HIS systems as those systems are normally complex systems and involve a high degree of technicality that requires the presence of the vendors or the developers after the system installation to train the staff at the starting stage and help them to overcome any possible problems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations